2007
DOI: 10.1097/meg.0b013e3282eeb53b
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic liver abscesses: mortality-related factors

Abstract: Mortality associated with PLA is high. The main risk factor for mortality is the development of sepsis and/or septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
59
3
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 17 publications
8
59
3
2
Order By: Relevance
“…Several studies to identify prognostic factors for case fatality in PLA patients have been performed, yet discrepancies exist regarding this issue [3,4,7,[9][10][11]29]. No other studies identifying prognostic factors for old PLA patients have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies to identify prognostic factors for case fatality in PLA patients have been performed, yet discrepancies exist regarding this issue [3,4,7,[9][10][11]29]. No other studies identifying prognostic factors for old PLA patients have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…With the advances in diagnostic techniques and therapeutic modalities, the incidence of PLA has increased and the case-fatality rate has gradually declined, but remains within the range of 6-35% [2][3][4][5][6][7][8][9][10][11]. Further, the mean age of PLA patients has increased since 1938 and PLA has become a disease of the middle-aged and elderly with a reported mean age S.-C. Chen et al…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the epidemiology has changed dramatically in recent years, with the annual increases in incidence being 5.6% and 6.4% in the United States and Taiwan, respectively. The overall mortality rates of PLA remain high, ranging from 2.5% to 19%, 24,6,7 and the mortality rate in Taiwan is approximately 8.3%. 8 Recently, PLA has been associated with an increased risk of malignancy, 911 subsequent infections, 1215 acute pancreatitis, 16 and stroke.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Underlying malignancy, besides diabetes mellitus and biliary tract disorders, is a common coexisting disease among PLA patients and accounts for 5% to 42% of these patients in various countries. 1,2,[6][7][8][9][10][11][12][13][14] In the literature, concomitant malignancy unlike other underlying disorders has been found to be a risk factor for PLA mortality.…”
Section: Introductionmentioning
confidence: 99%